2005
DOI: 10.3177/jnsv.51.361
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferation in Liver of Rats Fed Oxidized Frying Oil

Abstract: SummaryOxidized frying oil (OFO) activates peroxisome proliferator-activated receptor a (PPAR a) in vitro and in vivo. As most PPARa activators are also peroxisome proliferators (PP), this study was aimed at exploring whether OFO induces peroxisome proliferation in the liver of rats. Four groups of male weanling Sprague-Dawley rats were fed the following diets for 6 wk: a basal diet containing 5g/100 g fresh soybean oil (LSB), high-fat diets con taining 20g/100g of fresh soybean oil (HSB as a control), OFO (HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
(20 reference statements)
2
18
0
Order By: Relevance
“…Studies in rodents have shown that many of the effects induced by administration of FGF21 such as a reduction of liver and plasma TAG concentrations [10-12,18,19,31], a reduction of plasma cholesterol [10,13,31-33], an increase in HDL-cholesterol concentration [31], a reduction of adipose mass [15], or an increase of insulin sensitivity [34] are also induced by dietary oxidized fat. Previous studies have shown that dietary oxidized fats can even prevent an alcohol induced steatosis or the development of atherosclerosis [16,35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have shown that many of the effects induced by administration of FGF21 such as a reduction of liver and plasma TAG concentrations [10-12,18,19,31], a reduction of plasma cholesterol [10,13,31-33], an increase in HDL-cholesterol concentration [31], a reduction of adipose mass [15], or an increase of insulin sensitivity [34] are also induced by dietary oxidized fat. Previous studies have shown that dietary oxidized fats can even prevent an alcohol induced steatosis or the development of atherosclerosis [16,35].…”
Section: Discussionmentioning
confidence: 99%
“…OFO was prepared by frying dough sheets in soybean oil (President) at 205 6 5°C for four 6-h periods as previously described (1)(2)(3). The extent of oxidation was evaluated by the acid value (OFO, 2.841; SO, 0.056 KOH mg/g) and conjugated diene amounts (OFO, 3560; SO, 504 OD 233 units/g oil), values very similar to those obtained in our previous studies (1)(2)(3)7,8).…”
Section: Methodsmentioning
confidence: 86%
“…Although frequent consumption of fried food, inevitably accompanied by high fat intake, is causally related with obesity, cardiovascular disease, and cancer, we and others have shown that, in both in vitro and in vivo, oxidized frying oil (OFO) 4 is more potent than fresh oil in activating PPARa (1)(2)(3)(4). Accordingly, when rodents fed diets with equal amounts of OFO or fresh oil are compared, lower plasma and liver lipid concentrations (1,5,6), less adiposity (7,8), and lower proinflammatory responses in the vasculature (9) are observed in the OFO-fed group.…”
Section: Introductionmentioning
confidence: 99%
“…Catalase is a peroxisome enzyme which cleaves hydrogen peroxide. OFO causes peroxisome proliferation by activating PPARα [5] and this could be the cause of the increased levels of catalase protein in OFO-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of total cytochrome P450 monooxygenase (CYP) activity [3] by OFO suggests that OFO contains substances that need to be metabolized by CYPs in the liver. CYP1A1 [4] and CYP4A1 [5] protein levels and CYP4A1 and CYP2E1 mRNA levels [6] are also increased when rats are fed thermally oxidized dietary fat.…”
Section: Introductionmentioning
confidence: 99%